A. I. KUKHTENKO ON AVIATION SIMULATORS - Gulenko, V. P. (Problems of Informatization and Management, 2021)
I was fortunate enough to listen to lectures given by A. I. Kukhtenko in theoretical mechanics (1957), to defend an engineering diploma in front of the State Examination Commission, which included A.I. Kukhtenko, as well as directly work and become a specialist in technical cybernetics and information theory in the research laboratory (RL) of aviation simulators (AT), the scientific supervision of which was carried out by A. I. Kukhtenko for over twenty years.